2018
DOI: 10.1186/s12879-018-3404-2
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated transmission of Panton-Valentine leucocidin positive methicillin-resistant Staphylococcus aureus: the value of screening asymptomatic healthcare workers

Abstract: BackgroundThree patients hospitalised in the coronary care unit of a general district hospital (England, UK) were tested positive for Panton-Valentine leucocidin methicillin-resistant Staphylococcus aureus colonisation during their routine weekly screening for methicillin-resistant Staphylococcus aureus (MRSA). The isolates were indistinguishable and all three patients have previously had negative screening tests. The outbreak investigation team considered exploring the possibility of PVL-MRSA transmission fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…PVL-MRSA has been also linked to nosocomial infections in which hospital transmission of CA-MRSA had occurred in the US [40], highlighting the important source of CA-MRSA as a public health threat in hospitals. In low MRSA prevalence settings, healthcare workers may also serve as a reservoir of MRSA and an important potential source of transmission to patients as demonstrated by several studies [41,42]. Several EU-EEA countries are still reporting high levels of MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…PVL-MRSA has been also linked to nosocomial infections in which hospital transmission of CA-MRSA had occurred in the US [40], highlighting the important source of CA-MRSA as a public health threat in hospitals. In low MRSA prevalence settings, healthcare workers may also serve as a reservoir of MRSA and an important potential source of transmission to patients as demonstrated by several studies [41,42]. Several EU-EEA countries are still reporting high levels of MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…HCWs of three major hospitals of Peshawar district and the general population were screened for MRSA colonization in a study carried out in Pakistan. The study observed a high prevalence in nasal mucosa both in HCWs and in the general population as compared to colonization in the armpit [20].…”
Section: Discussionmentioning
confidence: 71%
“…This finding is in agreement with a study that identified the 'fear of stigmatization if confidentiality and anonymity protection fails' to be a challenge in staff MRSA screening. 7 'Subjective norms' seem to play an inferior role in predicting HCW behavior; only half of HCWs felt that they had been motivated by others to participate in the screening. Still, the invitation for screening by superiors might be beneficial because other studies have shown that counselling and emotional support from the decreeing authority is a facilitator for participation.…”
Section: Discussionmentioning
confidence: 99%